Understanding the Lung Disposition of Inhaled Compounds using the Bronchial Epithelial Cell Culture Model Calu-3 - Panduga, Vijender (2019)
Understanding the biological processes that control pulmonary drug retention is essential for designing novel inhaled therapeutics with optimized target site exposure in the lungs. However, due to lack of suitable experimental methods drug disposition in the lungs following inhalation remains poorly characterized. Establishing human airway cell culture models for such investigations may help creating microenvironment of the lungs allowing to gain understanding of inhaled drug distribution in the lungs at a cellular and subcellular level. In this direction, the current thesis aimed at applying a physiologically relevant human bronchial epithelial cell model Calu-3, for improving understanding of the role of two biological factors, i.e., transporter proteins and lysosomal sequestration, on the pulmonary disposition of inhaled molecules. Calu-3 cell layers grown under air-liquid interface culture conditions for 21 days were used for investigating inhaled drug uptake and permeability mechanisms. Lysosomal sequestration of inhaled molecules was assessed by measuring their cellular partition coefficient (Kp) in the presence of cytosol-lysosomal pH gradient disruptors. A cell-fractionation approach was also used for directly determining inhaled compound association with lysosomes. Lung retention following intra-tracheal administration in rats was determined for various molecules. Compound concentrations in in vitro and in vivo samples were quantified using liquid chromatography - tandem mass spectrometry. With an objective to study the transporter-mediated cellular disposition, ipratropium bidirectional transport as well as accumulation and release studies were performed in Calu-3 layers in presence or absence of a range of transporter inhibitors. Ipratropium showed a polarized transport across Calu-3 layers with a significantly higher permeability (Papp) in the basolateral to apical direction than in opposite side. The presence of efficient carrier-mediated uptake and efflux mechanisms for ipratropium was evident on the apical side of the cell layers. Acting in concert, apical transporters seem to promote the ‘luminal recycling’ of the drug and due to limited flux across the basolateral side, ipratropium appeared to permeate the airway epithelium predominantly through paracellular diffusion. Thus, these results in Calu-3 layers were able to reconcile conflicting absorption data in undifferentiated lung epithelial cells and in intact lungs previously reported for ipratropium. Measurements of Kp in Calu-3 cells for monobasic, dibasic, quaternary and zwitterion molecules reflected their lung tissue affinity and were in agreement with unbound drug volume of distribution (Vu, lung) reported in a rat lung slice model. Further, inhaled drug uptake and permeability in Calu-3 layers following pH-gradient disruption demonstrated the role of lysosomal sequestration as a retention mechanism across the airway epithelium. Finally, the cellular disposition mechanisms of compounds investigated in Calu-3 cell model, i.e. permeability and lysosomal association successfully explained their lung retention in vivo in rats. Overall, this work supports the application of the Calu-3 cell line for identifying compounds that are likely to be retained in the lung following pulmonary delivery, as an alternate to animal-based experiments. As Calu-3 model only represent cell types present in the bronchial epithelium, further studies with complex co-culture systems consisting of different cell types is advocated to simulate the complex lung physiology in vitro at the cellular level.